A Comparison of a Three Blade and Five Blade Wind Turbine in Terms of the Mechanical Properties Using the Q-Blade Software - Othman K. Zidane; YaseenH. Mahmood Mahmood (مجلة بغداد للعلوم)
Wind turbines deployed in utility-scale wind farms can support and meet future energy desires and also decrease carbon dioxide emissions by reducing energy requirements from fossil fuels. As the air heats up throughout the day, the wind velocity increases due to temperature gradients. This in turn produces a density pressure gradient, inducing air movement that a wind turbine encounters. Depending on ground topography, the wind can encounter and be directed in valleys and between and over hills as it flows and follows the curves of the earth. These topographies produce an increase in wind velocity at summits and ridges. In the current study, a small horizontal wind turbine rotor blade is designed to operate under low wind speed, by using the Q-Blade software. Based on the Blade Element Momentum method (BEM) and airfoil NACA3712, a three-blade rotor and a five-blade rotor are used based on turbine type and rotor size to generate mechanical power from wind power. A comparison and analysis of turbine power, power coefficient, and torque coefficient are carried out at low wind speed 1m/s-8m/s and highly accurate results are obtained. It is found that the best performance is gained when a three-bladed turbine rotor can work with a turbine power of 582W. As for the five-blade rotor, the turbine power obtained is (955W). It is also found that the design of a small horizontal wind turbine with five blades is more efficient than a turbine with three blades, suitable for working in areas with low wind speed and is of high efficiency compared to the size of the turbine.